SISTEM PENDIDIKAN ISLAM - Bakar, Abdul Syukur Abu (Universitas Islam Negeri Alauddin Makassar, 2020)
Education is a process of activities that are planned, practical and have goals to be achieved. Such is the importance of these goals, so it is not surprising that many serious studies have been found among experts on these goals. Various books that study about education, and always try to formulate goals, both in general and specifically. Islamic Education System there are familiar with the traditional education system instead of the cool, so that from this the researcher wants to review further about the Islamic education system so that it is able Implemented properly.